Potensi Etnomatematika Berbasis Budaya Lampung untuk Meningkatkan Karakter Cinta Budaya Mahasiswa Pendidikan Guru Sekolah Dasar - Destini, Frida; Efendi, Ujang; Muhisom, Muhisom; Perdana, Dayu Rika; Pangestu, Deviyanti; Profithasari, Nindy (Didaktika, 2022)
Mathematics is a subject that has a close relationship with everyday human life. The meaning of the existence of mathematics is still rarely felt directly by students so that mathematics becomes abstract and tends to be full of meaningless numbers. In fact, in fact mathematics has many benefits in everyday life and can be more easily reasoned and understood and memorable if we have the sincerity to understand. Culture-based learning is a strategy for creating learning environments and designing learning experiences that integrate culture as part of the learning process. Through ethnomathematics, learning will be more memorable because it introduces local traditions and cultures that are still recognized and practiced by certain community groups. The type of research used by the author in this study is descriptive qualitative. The study was conducted to explore information about ethnomathematics based on Lampung culture using sticks to increase the cultural love of elementary school teacher education students. Technique The instrument used in this study is a non-test technique. The results showed that ethnomathematical learning can increase student interest by a percentage of 92% and can be used as an alternative to help students learn multiplication material in mathematics and can increase students' sense of cultural love.